Statistical Relative Uniform Convergence in Dually Residuated Lattice Totally Ordered Semigroups - Demirci, Kamil; Yıldız, Sevda (Sarajevo Journal of Mathematics, 2020)
We define the notions of statistical relative uniform convergence and statistical relative uniform Cauchy in dually residuated lattice totally ordered semigroups (simply, DRlt-semigroups). Then, we give some basic properties for statistically relatively uniform convergent sequences. Also, we introduce statistical relative uniform limit points and cluster points in DRlt-semigroups, then the relations between these and limit points of the sequence are given.